مهددات شبكات البنوك من خلال منظور كل من (بنك السودان المركزي، بنك الخرطوم، بنك ام درمان الوطني) - محمود إبراهيم حمد; محمود علي أحمد (White Nile Journal for Studies and Research, 2013)
The Importance of this paper comes from the necessary of knowing the risks which faces the net work banking systems, A survey has been prepared and distributed to selected banks, Such as Omdurman National Bank, Bank of Khartoum, and Bank of Sudan and its branches In order to know the assets which need protection in the network and from sources has to protect the same, and the Hackers of network system and ways of networks which may attacked Electronic Banking, network risks, security network Key words